2009
DOI: 10.18060/168
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Sexual Minority Issues in Social Work Education: A Curriculum Framework

Abstract: This paper will explore a curriculum framework that explicitly addresses the reduction of heterosexism as a means to produce students that are culturally competent to practice with the lesbian, gay, bisexual, transgender, and queer (LGBTQ) community. Van Den Bergh and Crisp (2004) place great importance on addressing beliefs/attitudes, knowledge, and skills when broaching culturally competent practice with the LGBTQ population. Beliefs/attitudes, knowledge, and skills in an educational approach will be advocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Emerging social workers must be educated and prepared to engage with clients in discussions and decisions around sexual behavior. In conclusion, findings of the present study support the call given (Ramseyer Winter, 2015;McKay, 2015;Gezinski, 2009;Van Den Bergh & Crisp, 2004) for more sexual behavior education within the social work curriculum.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Emerging social workers must be educated and prepared to engage with clients in discussions and decisions around sexual behavior. In conclusion, findings of the present study support the call given (Ramseyer Winter, 2015;McKay, 2015;Gezinski, 2009;Van Den Bergh & Crisp, 2004) for more sexual behavior education within the social work curriculum.…”
Section: Resultssupporting
confidence: 86%
“…Currently, the Educational and Practice Standards (EPAS) from the Council on Social Work Education (CSWE) do not require that social work programs at any level (BSW or MSW) include sexuality education or sexual health education as part of classroom or field placement curriculum (Council on Social Work Education, 2008). The call for curriculum that includes human sexuality education occurred as early as the 1970s (e.g., Brashear, 1976;Gochros & Schultz, 1972), and has continued throughout the past few decades (e.g., Ramseyer Winter, 2015;McKay, 2015;Gezinski, 2009;Van Den Bergh & Crisp, 2004;O'Neill, 2016). One study reports that graduate social work students reported attempts to include discussion and/or study of sexuality as part of their program, and subsequently were encouraged to abandon these topics by social work faculty (McCave, Shepard, & Ramseyer Winter, 2014).…”
Section: Sexuality Education In Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet these topics remain mostly absent from both classroom-based curricula and fieldbased trainings. Scholars have more recently joined this call to action, showcasing the need for diverse topics in the realm of sexuality and health to be formally covered in social work education (Gezinski, 2009;Ramseyer Winter, 2015;Van Den Bergh & Crisp, 2004).…”
Section: Reproductive and Sexual Rights As Human Rightsmentioning
confidence: 99%
“…This would concurrently support individuals in exploring and grappling with their existent beliefs and attitudes (Gezinski, 2009;Van Den Bergh & Crisp, 2004). Such efforts may alleviate concerns discussed by bachelor's and master's of social work students in that they feel inadequately prepared and undersupported to engage with issues of sexuality that may arise while working with clients in real-life settings (Laverman & Skiba, 2012;Logie, Bogo, & Katz, 2015;Newman, Bogo, & Daley, 2009).…”
Section: Reproductive and Sexual Rights As Human Rightsmentioning
confidence: 99%